Estimation the cost of Environment degradation due to Air pollution in Kirkuk city. - Mohamed A. Najemalden (Kirkuk Journal of Science, 2016)
The cost of Environmental degradation (COED) is one of the hidden cost, that will not appear as direct cost , rather than it will cause indirect effects like health and economic effects, for example Air burden diseases and degradation of agriculture products. (COED) consists of calculation/estimation the financial cost caused by Environmental degradation (present time &future).the final estimation of (COED) is represented as percentage of Gross domestic product (GDB) for a country. This research concluded estimation of (COED) caused by Air pollution in Kirkuk governorate north of Iraq (one of the biggest oil production cities in Iraq), the same scientific method adopted by World Bank was applied in this research. The results showed that (COED) for Air pollution in Kirkuk equal to 68.8 billion I.Q.D which represent 12% of Kirkuk (GDB) for 2013. The results of this research represent 4.5% of the (COED) from Air pollution (for all Republic of Iraq Area).Urgent action must be taken to treat Air pollution resources in Kirkuk urgently.